Bioactive Triterpenoid Saponins From the Seeds of Aesculus chinensis Bge. var. chekiangensis - Zhang, Nan; Wei, Shuxiang; Cao, Shijie; Zhang, Qiang; Kang, Ning; Ding, Liqin; Qiu, Feng (Frontiers in Chemistry, 2020)
Phytochemical investigation of Aesculus chinensis Bge. var. chekiangensis (Hu et Fang) Fang obtained 33 triterpenoid saponins, including fourteen new ones, Aesculiside C -P (1-14). The structure elucidations were performed through comprehensive MS, 1D and 2D-NMR analysis, and their absolute configuration were unambiguously determined by X-ray diffraction analysis as well as Mo 2 (OAc) 4 -induced ECD method for the first time. All the substances were examined for their cytotoxic activities against three tumor cell lines, Hep G2, HCT-116 and MGC-803. Of these, compounds 8, 9, 14-16, 18, 22 exhibited potent cytotoxicities against all cell lines with IC 50 of 1.77 to 20.51 μM, while compounds 3, 6, 7, 17-19, 20, 24, 28 dipicted moderate activity (IC 50 12.92 to > 40 μM). On these basis, the preliminary structure-activity correlations were also discussed. Meanwhile the neuroprotective properties of triterpenoid saponins from Aesculus genus were evaluated for the first time. Among them, compounds 1, 4, 12, 20, 22, 25, 29, 31 exhibited moderate activities against C O Cl 2 -induced PC12 cell injury.